Foliage overhanging water, probably near Kahiltna River, Alaska, July 1914 - University of Washington Libraries. Special Collections Division.
McPherson number: K60 PH Coll 495.1-15d Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.